Characteristics and Physical Workload of Nurses on Night Shifts with Work Fatigue - Octavia, Ari Dian; Nurmayanti, Demes; Darjati; Winarko; Suryono, Hadi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
At RSUD Sidoarjo, it was discovered that 44% of nurses experienced fatigue. Fatigue occurs due to several factors, one of which is the physical workload. The objective of this study is to examine the physical workload and characteristics of nurses on night shifts on the fatigue of inpatient tulip nurses at RSUD Sidoarjo in 2022. The number of samples was 30 respondents with the sampling technique encompassing all of population of nurses on night shifts. The results demonstrated that there was no influence between physical workload on work fatigue with a value of 0.717, as well as characteristics incorporating age, length of service and gender which had no effect on work fatigue with a value of 0.636, respectively; 0.747 and 0.235. The result of the study indicates that workload, age, working period, and gender of nurses have no effect on nurses' work fatigue. The conclusion is there was no influence between physical workload and characteristics of nurses on night shifts on the fatigue of inpatient tulip nurses at RSUD Sidoarjo in 2022. It is recommended that future researchers will conduct research on nurse fatigue employing various variables such as mental workload on nurses, hospital physical environment, distance of residence, and marital or family status.